Assessment of the impact of desertification impact on the natural environment and the resident population of the Brazilian semiarid region by means of an integrated geographical database - Vieira, Rita Marcia da Silva Pinto; Sestini, Marcelo Francisco; Tomasella, Javier; Rodriguez, Daniel Andrés; Barbosa, Alexandre Augusto; Campello, Francisco Carneiro Barreto; Santana, Marcos Oliveira; Ometto, Jean Pierre Henry Balbaud; Valles, Giane de Fatima (Sustainability in Debate, 2016)
The Northeast Region of Brazil is strongly characterized by regional differences such as high rates of illiteracy, low income levels, migration to urban centers, social exclusion, among others. Besides cultural and economic differences, the region is affected by land degradation and desertification exacerbated by anthropogenic factors. Understanding landscape changes and how they affect the vulnerability of the population poses a scientific challenge, because these changers take place at wider spatial and temporal scales. Therefore, the development of a geographical database that can enable the integration and assimilation of bio-geophysical and socioeconomic information is crucial for understanding those changes. More important than the development of the tool is learning how to perform a joint analysis of the information generated. This paper describes the development of a methodology that generates an early drought and desertification warning system and analyzes the population's vulnerability to those changes, by integrating information related to land degradation. The goal is to enable analyses by decision makers allow the implementation of measures in areas where both processes are happening in a more intense manner.